Accumulation of Effector Memory CD8+ T Cells in Nasal Polyps. Issue 5 (September 2013) - Pant, Harshita; Hughes, Amy; Miljkovic, Dijana; Schembri, Mark; Wormald, Peter; Macardle, Peta; Grose, Randall; Zola, Heddy; Krumbiegel, Doreen
Background: T lymphocytes are prevalent in sinus mucosa and are implicated in chronic rhinosinusitis (CRS) pathogenesis. However, the major T-cell subpopulations, helper (CD4 + ) and cytotoxic (CD8 + ), have not been adequately examined in CRS. This study was designed to characterize human sinus mucosa and peripheral blood (PB) CD4 + and CD8 + T cells and their level of differentiation in CRS with nasal polyps (NPs), CRS without NPs, and control patients. Methods: A prospective study was performed. Percentages of CD4 + and CD8 + T cells and their levels of differentiation were analyzed in sinus mucosa and PB by flow cytometry. Cell populations were defined as naive, central memory, effector memory, and effector T cells using cell surface markers CD45RA, CD62L, and CD27. The influence of coexisting allergy, sinus eosinophilic mucus (EM), and culture results were examined. Results: In all patients, sinus mucosa had a lower percentage of CD4 + and a higher percentage of CD8 + T cells compared with PB. However, CRS with NPs (n = 86) had a significantly higher percentage of mucosal CD8 + T cells compared with CRS without NPs (n = 40) in control (n = 13) patients (p < 0.0001). Effector memory T cells were increased in sinuses compared with PB in all patients; however, the percentage of effector memory CD8 + T cells was greatest in CRS with NP mucosa (p = 0.002). Surprisingly coexisting allergy or culture results did not influence the mucosal T-cell phenotype. CRS with NP patients with sinus EM had a significantly higher percentage of mucosal CD8 + T cells. Conclusion: Sinus mucosa in CRS with NPs is characterized by a significant enrichment of CD8 + T cells and a relative deficiency of CD4 + T cells. The majority of NP CD8 + T cells had a terminally differentiated, mature, effector memory phenotype, which raises the question, whether these cells are pathogenic or appear as a consequence of inflammation, independent of the presence of allergy or positive microbial culture.